1989
DOI: 10.1002/jpln.19891520212
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Turnover in the Rhizosphere

Abstract: Considerable progress has been made during the last decade towards understanding and quantifying the input and turnover of plant carbon in the rhizosphere. This was made possible by the development (partially by the authors) and combination of appropriate new methods, such as: –homogeneous labelling of whole plants with 14C –distinction between root and microbial respiration –separation of soil zones of known distances from the roots –determination of microbial soil biomass. These methods were applied to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(30 citation statements)
references
References 18 publications
4
22
0
3
Order By: Relevance
“…Increased secretion of oxalic acid with increase in crop growth interval has also been reported earlier [14]. It is largely accepted that up to 20-30 % of total carbon assimilated by higher plants is released in the rhizosphere as diverse exudates including CO 2 respired [15]. Varieties also had a significant effect on secretion of oxalic acid in soil.…”
Section: Secretion Of Oxalic Acidsupporting
confidence: 64%
“…Increased secretion of oxalic acid with increase in crop growth interval has also been reported earlier [14]. It is largely accepted that up to 20-30 % of total carbon assimilated by higher plants is released in the rhizosphere as diverse exudates including CO 2 respired [15]. Varieties also had a significant effect on secretion of oxalic acid in soil.…”
Section: Secretion Of Oxalic Acidsupporting
confidence: 64%
“…Pulse 5,6 or continuous labelling of above-ground plant parts has frequently been used to distinguish between humus-derived and root-derived CO 2 and to quantify rhizodeposition. [7][8][9] Pulse labelling, compared with continuous labelling, has the advantage of being easier to handle, provides more information on the recent photosynthate distribution at specific developmental stages of plants, and can be used for kinetic investigations of 14 CO 2 evolution from the soil. The results obtained by pulse labelling correspond to the relative distribution of assimilated C at the moment of labelling.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal conditions, 12 to 54% of the carbon fixed by photosynthesis is released into the soil by the roots [26,27,36,46]. Lekkerkerk et al [32] showed that the root-derived, easily biodegradable compounds of wheat roots increased under a CO 2 -enriched atmosphere.…”
Section: Introductionmentioning
confidence: 99%